The Paleobiolinguistics of Maize (Zea mays L.) - Brown, Cecil H.; Clement, Charles R.; Epps, Patience; Luedeling, Eike; Wichmann, Søren (Ethnobiology Letters, 2014)
Paleobiolinguistics is used to determine when and where maize (Zea mays) developed significance for different prehistoric groups of Native America. Dates and locations of proto-languages for which maize terms reconstruct generally accord with crop-origin and dispersal information from plant genetics and archaeobotany. Paleobiolinguistic and other lines of evidence indicate that human interest in maize was extensive millennia before the widespread development of a village‐farming way of life in the New World.